Redução do abortamento de vagens e produtividade de plantas de soja tratadas com benziladenina - (:unkn) unknown (Universidade Estadual de Goiás, 2014)
The abscission of flowers and pods is a limiting factor in the productivity of soybean. The reduction of the abortion may result in increased pods number, and thus lead to a significant increase in grain yield. This study was carried out to evaluate the effect of benzyladenine in the reduction of abortion of soybean pods. The study was conducted at Panorama Farm, located in the municipality of Ipameri, Goiás. The soil of the experimental area was classified as Red Yellow Latosol. After soil analysis, was performed fertilization and pH correction according to technical recommendations for the culture. The soybean planting Pioneer 98Y12 RR was held in late November, during the rainy season. Five treatments were used with 0, 100, 200, 300 and 400 mg L -1 benzyladenine applied to R2 phenological stage, solution volume of 200 L ha-1 . The experiment was conducted following the randomized complete block design with five replications. The experimental plot was 3 x 2 m and about 90 plants operated at distances of 0,5 m between rows and 10 plants per linear meter. The benzyladenine application provided a significant increase in the productivity of all species to the concentrations that were used, in particular, 200 mg L-1 with maximum gain in productivity at around 17%. The increase in productivity was determined more decisively by the largest number of total fixed pods in plants due to the reduction of abortion in the three canopy positions (lower, middle and upper) of soybean plants. Other factors contributing to increased productivity were the highest number of seeds per plant, higher seed weight and diameter and can therefore, the application of benzyladenine be considered as a promising technology for the production of soybean.
Keywords: Regulador de crescimento; Floração; Rendimento de grãos; Growth regulator; Flowering; Grain yield; CIENCIAS AGRARIAS